The ω6-fatty acid, arachidonic acid, regulates the conversion of white to brite adipocyte through a prostaglandin/calcium mediated pathway - Pisani, Didier; Ghandour, Rayane A.; Beranger, Guillaume E.; Le Faouder, Pauline; Chambard, Jean-Claude; Giroud, Maude; Vegiopoulos, Alexandros; Djedaini, Mansour; Bertrand-Michel, Justine; Tauc, Michel; Herzig, Stephan; Langin, Dominique; et al. (Molecular metabolism, 2014)
Brite adipocytes are inducible energy-dissipating cells expressing UCP1 which appear within white adipose tissue of healthy adult individuals. Recruitment of these cells represents a potential strategy to fight obesity and associated diseases.
Gesehen am 20.10.2020